Relationships of Adenine Nucleotide Metabolism to Platelet-Collagen Adhesion - Morin, Robert J; Chen, Albert F T (Thrombosis and Haemostasis, 1978)
Adhesion of platelets to collagen fibrils in a stirred system was inhibited by preincubation of platelets with combinations of 2-deoxy-D-glucose and oligomycin or antimycin. The inhibition of adhesion was associated with a decrease in metabolic ATP to 6% of control levels. Without metabolic inhibitors, platelets adherent to collagen fibrils were found to have catabolized approximately 57% of their metabolic ATP, and converted a major part of this to IMP. Storage pool ATP and ADP contents were also diminished in the adherent platelets. Pretreatment with imipramine resulted in 76% inhibition of the release reaction, but only 5% inhibition of adhesion. Imipramine-treated platelets that were adherent to collagen showed significant depletion of metabolic ATP, but markedly diminished conversion of ATP to IMP as compared to control adherent platelets. Inhibition of deamination of platelet AMP by coformycin or erythro-9-(2-hydroxy-3-nonyl) adenine (EHNA) did not inhibit adhesion, although platelets adherent to collagen after treatment with these agents showed depletion of metabolic ATP. These studies suggest that adhesion is an energy dependent process, occurring independently of release, and not associated with conversion of ATP to IMP. The energy dependent portions of the adhesion process are probably disc to sphere transformation and pseudopod formation, the ATP threshold requirement is relatively low, and the ATP utilized can probably be regenerated during the adhesion process via glycolysis and oxidative phosphorylation.